INHIBITORY OF SOURSOP LEAVES (Annona muricata L.) EXTRACT AGAINST Malassezia furfur GROWTH - Rike Rizqilah; Dadan Ramadhan Apriyanto; Ruri Eka Maryam Mulyaningsih (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Malassezia furfur in certain conditions can turn into a pathological phase, from the yeast phase to the mycelia phase that attacks the stratum corneum. Malassezia furfur is one of the causes of Pityriasis versicolor. The prevalence of pityriasis versicolor in Indonesia is quite high at around 40- 50%. Several studies suggested that soursop leaves (Annona muricata L.) contains active substances with anti-fungal properties. This study aims to determine the inhibition of soursop leaves (Annonamuricata L.) extract against the growth of Malassezia furfur. Methods: This study was an experimental study with Post-test Only Control Group Design. Malassezia furfur fungi is used as subject in this study and ethanol extract of soursop leaves as a natural antifungal against Malassezia furfur. The concentrations of extract tested were 100%, 80%, 60%, 30%. Miconazole 2% was used as a positive control while DMSO 10% was used a negative one. The result of the study was analyzed by descriptive analysis which showed by increasing average diameter ofantifungal. Results: The results showed that soursop leaves (Annona muricata L.) extract had inhibitory effect on the growth of Malassezia furfur fungi at 100% concentration of 2.50 mm, 80% at 1.50 mm, 60% at 0.47 mm, 30% concentration at 0.25 mm and positive control of 14.50 mm. While as negative control, no inhibition zones were formed on SDA media. Conclusion: Soursop leaves (Annona muricata L.) extract can inhibit the growth of Malassezia furfur, but the formed inhibition zone is weak. Further research is needed to found the best type of antifungal metabolites to maximize antifungal effects. Keywords: Soursop leaves extract, Annona muricata L. , Malassezia furfur